The Correctional System Revitalization: the Understanding Required to Revitalize Convicts'Correctional Facilities - Sulistyanta, Sulistyanta; Shaifu, Awwal Muhammad (Faculty of Law, Universitas Sebelas Maret, 2021)
This research describes the individualization of convict coaching and the special penitentiary for certain convicts. It also analyzes the understanding required to revitalize convicts' correctional facilities, which assess changes in treatment regarding those with